Pap‐tests with non‐hyperchromatic dyskariosis are often associated with squamous intraepithelial lesions of the cervix uteri with eosinophilic features. Issue 10 (13th July 2016) - Bellisano, Giulia; Ambrosini‐Spaltro, Andrea; Faa, Gavino; Ravarino, Alberto; Piccin, Andrea; Peer, Irmgard; Kasal, Armin; Vittadello, Fabio; Negri, Giovanni
Abstract : Background: Squamous intraepithelial lesions of the cervix uteri with eosinophilic features (eosinophilic dysplasia, ED) are a peculiar type of dysplasia with metaplastic phenotype which was described in histological specimens. The cytological features of these lesions have not been studied yet. Methods: Histological samples from 66 women with features of ED and positive p16 INK4a staining were included in the study. Within the previous year, all women had at least one pap‐test, whose features were recorded and compared with 31 control samples with high‐grade dysplasia of usual type. Results: The previous pap‐test showed high‐grade dysplastic cells with non‐hyperchromatic nuclei in 56/66 (84.8%) cases and metaplastic features in 60/66 (90.9%) cases. Conversely, the dysplastic cells of the usual lesions showed non‐hyperchromatic nuclei in 6/31 (19.4%) and metaplastic features in 4/31 (12.9%) cases. Statistical analysis showed significant differences in distribution of the non‐hyperchromatic nuclei (P < 0.001), metaplastic features (P < 0.001), presence of both non‐hyperchromatic nuclei and metaplastic features (P < 0.001) and usual dysplastic features (P < 0.001) among the study and control groups. Conclusions: A high‐grade squamous intraepithelial lesion with non‐hyperchromatic nuclei or metaplastic features is often found in the pap‐test previous to the histological diagnosis of ED and may represent the cytologic correlate of this particular type of dysplasia. Diagn. Cytopathol. 2016;44:783–786. © 2016 Wiley Periodicals, Inc.